Stressed Vowel Duration and Phonemic Length Contrast - Ciszewski, Tomasz (Research in Language, 2012)
It has been generally accepted that greater vowel/syllable duration is a reliable correlate of stress and that absolute durational differences between vowels underlie phonemic length contrasts. In this paper we shall demonstrate that duration is not an independent stress correlate, but rather it is derivative of another stress correlate, namely pitch. Phonemic contrast, on the other hand, is qualitative rather than quantitative.These findings are based on the results of an experiment in which four speakers of SBrE read 162 mono-, di- and trisyllabic target items (made of CV sequences) both in isolation and in carrier phrases. In the stressed syllables all Southern British English vowels and diphthongs were represented and each vowel was placed in 3 consonantal contexts: (a) followed by a voiced obstruent, (b) voiceless obstruent and (c) a sonorant. Then, all vowels (both stressed and unstressed) were extracted from target items and measured with PRAAT.The results indicate that stressed vowels may be longer than unstressed ones. Their durational superiority, however, is not stress-related, but follows mainly from vowelintrinsic durational characteristics and, to some extent, from the prosodic context (i.e. the number of following unstressed vowels) in which it is placed. In CV1CV2 disyllables, when V1 is phonemically short, the following word-final unstressed vowel is almost always longer. It is only when V1 is a phonemically long vowel that V2 may be shorter. As far as diphthongal V1 is concerned, the durational V1~V2 relation is variable. Interestingly, the V1~V3 relation in trisyllables follows the same durational pattern. In both types of items the rare cases when a phonemically short V1 is indeed longer than the word-final vowel involve a stressed vowel which is open, e.g. [æ,o], and whose minimal execution time is longer due to a more extensive jaw movement. These observations imply that both in acoustic and perceptual terms the realisation of word stress is not based on the durational superiority of stressed vowels over unstressed ones. When it is, it is only an epiphenomenon of intrinsic duration of the stressed vowel and extra shortness of nonfinal unstressed vowel.As far as phonemic length contrast is concerned, we observe a high degree of durational overlap between phonemically long and short vowels in monosyllabic CVC words (which is enforced by a greater pitch excursion), whereas in polysyllables the differences seem to be perceptually non-salient (>40 ms, cf. Lehiste 1970). This suggests that the differences in vowel duration are not significant enough to underlie phonological length contrasts.